Genome of Epinotia aporema granulovirus (EpapGV), a polyorganotropic fast killing betabaculovirus with a novel thymidylate kinase gene - Ferrelli, María Leticia (2012)
Background: Epinotia aporema (Lepidoptera: Tortricidae) is an important pest of legume crops in South America. Epinotia aporema granulovirus (EpapGV) is a baculovirus that causes a polyorganotropic infection in the host larva. Its high pathogenicity and host specificity make EpapGV an excellent candidate to be used as a biological control agent. Results: The genome of Epinotia aporema granulovirus (EpapGV) was sequenced and analyzed. Its circular double-stranded DNA genome is 119,082 bp in length and codes for 133 putative genes. It contains the 31 baculovirus core genes and a set of 19 genes that are GV exclusive. Seventeen ORFs were unique to EpapGV in comparison with other baculoviruses. Of these, 16 found no homologues in GenBank, and one encoded a thymidylate kinase. Analysis of nucleotide sequence repeats revealed the presence of 16 homologous regions (hrs) interspersed throughout the genome. Each hr was characterized by the presence of 1 to 3 clustered imperfect palindromes which are similar to previously described palindromes of tortricid-specific GVs. Also, one of the hrs (hr4) has flanking sequences suggestive of a putative non-hr ori. Interestingly, two more complex hrs were found in opposite loci, dividing the circular dsDNA genome in two halves. Gene synteny maps showed the great colinearity of sequenced GVs, being EpapGV the most dissimilar as it has a 20 kb-long gene block inversion. Phylogenetic study performed with 31 core genes of 58 baculoviral genomes suggests that EpapGV is the baculovirus isolate closest to the putative common ancestor of tortricid specific betabaculoviruses. Conclusions: This study, along with previous characterization of EpapGV infection, is useful for the better understanding of the pathology caused by this virus and its potential utilization as a bioinsecticide.